Dementia and the biopolitics of the biopic: From Iris to The Iron Lady. (May 2013) - Wearing, Sadie
This article considers the question of embodiment through a comparative analysis of two 'biopics', Iris (2001) and The Iron Lady (2011), which both feature eponymous characters that have, or had, dementia. Embodiment draws our attention to the representation of the body in the films themselves, and to the socially significant 'feelings' or affects that circulate within and are reproduced around them. Shame, disgust and aversion are socially devastating affects conventionally associated with stigmatised bodies including those of the cognitively impaired but attention to the 'feeling tone' (Ngai, 2005) in these films demonstrates that a more varied range of affects and embodied social knowledge is produced. Embodiment is thus a starting point to explore what is at stake in these films both in their authorisation of particular versions of public lives and for their significance for the cultural politics of representation in the context of explorations of personhood and dementia.